The The Relationship between Soft Sell Advertising and Online Purchase Intention - Salim, Siti Aisyah; Md Sofri, Nurul Adilah (Research in Management of Technology and Business, 2022)
Understanding customer’s needs and identifying factors that led to purchase intention is recognize as one of the mechanism could be used to ensure the success in business. Several approaches have been introduced to enhance customers’ purchase intention especially in online platform settings, and soft sell is one of the examples. Prior research has widely discussed the impact of soft sell advertising; however, studies that looked into soft sell advertising and purchase intention in the context of Malaysia still very lack. Thus, this study aims to identify the relationship between soft sell advertising and online purchase intention among generation Z (Gen Z). Theory of Reasoned Action (TRA) is used as the theoretical foundation for this study. About 111 UTHM students who are being categorized as Gen Z have participated in answering the survey questions. The data was collected by using a quantitative research method where self-administered questionnaires and online surveys have been applied. The data were analyzed by using Statistical Package for Social Science (SPSS) software to determine demographic information, variables and the relationship between soft sell advertising and online purchase intention.  From the analysis, it showed that the level of attitude toward the advertisement dimension towards online purchase intention is at a high range level. In terms of relationship, all dimensions have a positive significant relationship towards online purchase intention where attitude toward the advertisement has the highest correlation coefficient is 0.604. This study can be used by future researchers to have further understanding on how soft sell advertising works towards online purchase intention especially among different generations.